2021
DOI: 10.3390/cells10113249
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate and Class I Histone Deacetylase Inhibitors Promote Differentiation of Neonatal Porcine Islet Cells into Beta Cells

Abstract: Neonatal porcine islets-like clusters (NPICCs) are a promising source for cell therapy of type 1 diabetes. Freshly isolated NPICCs are composed of progenitor cells and endocrine cells, which undergo a maturation process lasting several weeks until the normal beta cell function has developed. Here, we investigated the effects of short-chain fatty acids on the maturation of islet cells isolated from two to three day-old piglets. NPICCs were cultivated with acetate, butyrate and propionate (0–2000 µM) for one to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…C4 suppressed nuclear factor kappa B (NF-κB) and inflammatory cytokine production by β cells [ 96 ]. Moreover, C4 had positive effects on the differentiation of pancreatic islet cells to β cells in vitro and promoted insulin secretion from pancreatic islets [ 97 , 98 ]. In nonobese diabetic (NOD) mice, long-term antibiotic treatment depleted SCFA-producing bacteria, accelerated disease activity and increased the diabetogenic intestinal microbiome [ 99 ].…”
Section: Dysbiosis Decreased Scfa Production and Leaky Gut In T1dmmentioning
confidence: 99%
“…C4 suppressed nuclear factor kappa B (NF-κB) and inflammatory cytokine production by β cells [ 96 ]. Moreover, C4 had positive effects on the differentiation of pancreatic islet cells to β cells in vitro and promoted insulin secretion from pancreatic islets [ 97 , 98 ]. In nonobese diabetic (NOD) mice, long-term antibiotic treatment depleted SCFA-producing bacteria, accelerated disease activity and increased the diabetogenic intestinal microbiome [ 99 ].…”
Section: Dysbiosis Decreased Scfa Production and Leaky Gut In T1dmmentioning
confidence: 99%
“…A possible mechanism involves butyrate inhibition of the recruitment of HDACs to the promoter by the transcription factors specificity protein 1/specificity protein 3 (Sp1/ Sp3), leading to histone hyperacetylation (112). In addition, studies have shown that, as a histone deacetylase inhibitor, butyrate promoted pancreatic b-cell differentiation, which was seen as having potential for the treatment of diabetes (114,115).…”
Section: Histone Deacetylases (Hdacs)mentioning
confidence: 99%
“… 73 These findings suggest a protective role for cardiac RGS4 in reverse remodeling and in mitigation of sympathetic nervous system hyperactivity induced by gut microbiota-derived nutrient metabolites, such as propionic and butyric acids. 73 , 77 Of note, ketone bodies like β-hydroxybutyrate have been reported to antagonize FFAR3, 76 , 80 so it appears that RGS4 can mimic (at least some of) the beneficial actions of ketone bodies in the heart.…”
Section: Therapeutic Potential Of Cardiac Rgs4mentioning
confidence: 99%